1995
DOI: 10.1179/joc.1995.7.5.463
|View full text |Cite
|
Sign up to set email alerts
|

Late Effects of Chemoradiotherapy in Pediatric Hodgkin’s Disease

Abstract: We treated 137 Turkish children with biopsy-proven Hodgkin's disease, followed up between the years 1964 and 1989. Most patients were treated and were in advanced stage with histological subtype of mixed cellularity (67.5%). Radiotherapy (Mantle form) and/or MOPP, ABVD and OPPA combination chemotherapy regimens were used in 75.84% of patients. The follow-up period in these patients ranged from 5 to 24 years. The late effects in 28 patients who were evaluated for the late sequelae of chemoradiotherapy are prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Common late complications of childhood cancers after treatment include neurological, cardiac, pulmonary and gonadal disorders, reduction in bone mass, defective bone and soft tissue development, and increased susceptibility to secondary malignant tumors (1,2,3,4,5,6,7,8,9). Hyperthyroidism including Graves’ disease, thyroiditis, hypothyroidism, thyroid nodules and thyroid cancers are the most commonly encountered thyroid gland disorders that are known to be related with radiotherapy (6,10,11,12,13). The objective of this study was to evaluate thyroid function in pediatric Hodgkin’s lymphoma patients in complete remission with chemotherapy and radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Common late complications of childhood cancers after treatment include neurological, cardiac, pulmonary and gonadal disorders, reduction in bone mass, defective bone and soft tissue development, and increased susceptibility to secondary malignant tumors (1,2,3,4,5,6,7,8,9). Hyperthyroidism including Graves’ disease, thyroiditis, hypothyroidism, thyroid nodules and thyroid cancers are the most commonly encountered thyroid gland disorders that are known to be related with radiotherapy (6,10,11,12,13). The objective of this study was to evaluate thyroid function in pediatric Hodgkin’s lymphoma patients in complete remission with chemotherapy and radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…S1 . Most studies reported that the majority of HL survivors developed or maintained normal and regular menstrual cycles (median percentage of HL survivors with regular cycle 100%, range 79–100%, nine studies; 168 patients) ( Horning et al , 1981 ; Whitehead et al , 1982 ; Andrieu and Ochoa-Molina, 1983 ; Perrone et al , 1989 ; Hudson et al , 1993 ; Gözdasoglu et al , 1995 ; Madsen et al , 1995 ; Donaldson et al , 2007 ; Zaletel et al , 2010 ). Hudson et al (1993) mentioned that three patients developed amenorrhea during therapy but resumed spontaneous menses 2–4 years after completion of therapy.…”
Section: Resultsmentioning
confidence: 99%
“…These rates are very similar to pregnancy outcomes in the general population (Gnoth et al 2003 ; Wang et al 2003 ; Wesselink et al 2017 ). Most previous (cohort)studies mentioned number of female HL survivors achieving pregnancy or a live birth during follow up, without evaluating their wish to conceive, time to conceive or other fertility-related factors that may affect their reproductive potential (Beek et al 2007 ; Drechsel et al 2023 ; Fernandez-Pineda et al 2018 ; Gözdasoglu et al 1995 ; Green and Hall 1988 ; Horning et al 1981 ; Licht et al 2021 ; Mackie et al 1996 ; Madsen et al 1995 ; McCullough et al 2010 ; Papadakis et al 1999 ; Perrone et al 1989 ; Reulen et al 2009 ; Swerdlow et al 1996 ; Sy Ortin et al 1990 ; van der Kaaij et al 2012 ; Wilimas et al 1980 ). Among the two studies who specifically assessed pregnancy rates in females attempting pregnancy after diagnosis, reported pregnancy rates were comparable to our observations (77% of 26 survivors and 81% of 218 studied survivors, respectively) (Horning et al 1981 ; van der Kaaij et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%